2009
DOI: 10.5194/nhess-9-1259-2009
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of ionospheric plasma perturbations before Wenchuan earthquake

Abstract: Abstract. Based on data recorded by the French DEME-TER satellite, plasma perturbations have been analyzed before the Wenchuan 8.0 earthquake which occurred on 12 May 2008. Using the revisited orbits, the seasonal variations of the O + density at daytime and nighttime were obtained respectively. There mainly exist two kinds of shapes of O + density, with peak values in the Northern Hemisphere during May to September and reversely in the Southern Hemisphere during other months. Analysis on local daytime O + den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 14 publications
(18 reference statements)
2
47
0
Order By: Relevance
“…The strong seismotelluric current is thought to run mainly along the Longmenshan fault and electromagnetic oscillations, induced by the current and predominated by ULF frequency band, propagate up to the ionosphere and give rise to perturbations of ionospheric parameters. Some of these parameters have been investigated, such as GPS TEC and f0F2 (Yu et al, 2009;Xu et al, 2010;Akhoondzadeh et al, 2010), DEMETER satellite O+ density (Zhang et al, 2009b), electron density and electron temperature (Zeng et al, 2009), etc. Fortunately, all of these study results present a climax on 9 May 2008 and this indicates a LAIC or interaction aroused by these electromagnetic signals prior to the Wenchuan event.…”
Section: Discussionmentioning
confidence: 99%
“…The strong seismotelluric current is thought to run mainly along the Longmenshan fault and electromagnetic oscillations, induced by the current and predominated by ULF frequency band, propagate up to the ionosphere and give rise to perturbations of ionospheric parameters. Some of these parameters have been investigated, such as GPS TEC and f0F2 (Yu et al, 2009;Xu et al, 2010;Akhoondzadeh et al, 2010), DEMETER satellite O+ density (Zhang et al, 2009b), electron density and electron temperature (Zeng et al, 2009), etc. Fortunately, all of these study results present a climax on 9 May 2008 and this indicates a LAIC or interaction aroused by these electromagnetic signals prior to the Wenchuan event.…”
Section: Discussionmentioning
confidence: 99%
“…On 9 May, just 3 days before the Wenchuan 8.0 earthquake, TEC and foF2 of GPS observations, electron density and ion density of DEMETER satellite were subjected to an abrupt increase or decrease with amplitude being up to 40 %-80 %. The spatial distributions of the anomalous and extreme reductions and enhancements indicate that the earthquake preparation area is about 1650 km and 2850 km from the epicenter in the latitudinal and longitudinal directions, respectively (Zhao et al, 2008;Yu et al, 2009;Liu et al, 2009;Zeng et al, 2009;Lin et al, 2009;Akhoondzadeh et al, 2010;Zhang et al, 2009;Xu et al, 2010Xu et al, , 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Several case studies have shown that ionospheric signatures associated with earthquakes often appeared over the region near the epicenter within a short time period before earthquakes (Parrot and Mogilevsky, 1989;Serebryakova et al, 1992;Chmyrev et al, 1996;Trigunait et al, 2004;Parrot et al, 2006;Sarkar et al, 2007Sarkar et al, , 2011Sarkar andGwal, 2010, Liperovskaya et al, 2011). Many anomalous phenomena have already been recorded by DEMETER and reported by several workers (Parrot et al, 2006;Sarkar et al, 2007;Zhang et al, 2009;Akhoondzadeh et al, 2010).…”
Section: Introductionmentioning
confidence: 77%